2012
DOI: 10.1002/jmri.23876
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficacy of MRI for detection of changes in bone morphology in a mouse model of bone injury

Abstract: The RARE sequence was the most suitable for MRI bone imaging. It enabled the detection of hard and even soft tissue changes. These findings suggest that MRI could be an effective imaging modality for assessing changes in bone morphology and pathobiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Moreover, MRI provides more information on the tissues surrounding the fractured area, including bone marrow, muscles, periosteum and fat [810]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, MRI provides more information on the tissues surrounding the fractured area, including bone marrow, muscles, periosteum and fat [810]. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Baron et al described time dependent changes in quantitative MRI (qMRI) measurements of fractures in adult subjects as a precursor for a quantitative fracture dating approach. Therefore, MRI could become the more adequate method for the diagnosis and dating of a fracture [8,10]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the limitations of that study are firstly, that the mice were sacrificed before the MRI examination and therefore the tissue contrast may have differed from the in vivo situation, and secondly, the limited spatial resolution possible with the 4.7-Tesla system used in this study. Taha et al [10] investigated different MR imaging techniques at 9.4-T field strength and showed that a proton density weighted TSE sequence performed best for the evaluation of bone healing. This method was able to discriminate between bone and soft tissue, including the medullary space and granulation tissue at the injury site at a higher contrast than μCT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no studies reported testing in vivo MRI during endochondral fracture healing in mice. Previous work includes post mortem MRI in mice with articular fractures [9] and in vivo MRI to monitor intramembranous bone-defect healing [10]. Both studies showed promising results, despite limited spatial resolution and tissue contrast.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, MRI is used in the clinical setting to identify cartilage defects and may be used to identify HO, a lesion that forms through endochondral ossification, prior to ossification[ 3 , 21 , 22 ]. MRI may also have potential in detecting changes regular bone morphology induced by HO[ 23 , 24 ]. Similarly, positron emission tomography (PET) scans allow for identification of foci with high metabolic activity[ 25 ].…”
Section: Discussionmentioning
confidence: 99%